Implementasi Pendekatan Teaching at the Right Level dalam Meningkatkan Hasil Belajar Siswa SDN Jemur Wonosari 1 Surabaya - Ikma Qusnul Nazila; Akhwani Akhwani; Sianah Sianah (STKIP AL HIKMAH SURABAYA, 2023)
The research conducted by researchers, namely classroom action research (PTK), aims to determine the application of the Teaching at The Right Level (TaRL) approach to increasing students' understanding of length measurement material using non-standard units. Data collection techniques are observation and tests. The test was carried out 3 times consisting of pre-cycle, cycle 1 and cycle 2. The method used in this research was simple statistics and observation sheets. The subjects of this research were class IA students at SDN Jemur Wonosari 1 Surabaya with a total of 28 students. The application of the TaRL approach to class IA mathematics subjects at SDN Jemur Wonosari I Surabaya can be said to be successful. This is based on the results of observations of educators' activities in cycle I, namely 74%, then in cycle II it was 92%. Then, the results of observing student activities in cycle 1 were 78%, then increased to 90% in cycle 2. Apart from that, the increase in learning outcomes for class IA students at SDN Jemur Wonosari 1 Surabaya experienced a significant increase starting from pre-cycle which was 25 % then in cycle 1 it was 64% and increased in cycle 2 to 89%.